Morphology of the first zoea of Chaceon affinis (A. Milne-Edwards & Bouvier, 1894) and occurrence of Chaceon spp. larvae (Decapoda: Brachyura: Gerynonidae) in the Canary Islands waters, Northeastern Atlantic - Landeria, José M.; Tamura, Hiroaki (Zootaxa, 2018)
The morphology of the first zoea stage of Chaceon affinis is described and illustrated in detail for the first time. Morphological comparison with the corresponding stage of other known species of Geryonidae allowed the differentiation between the genera Chaceon and Geryon, although it was impossible to distinguish among species of Chaceon using larval morphology. Thus, geryonid larvae collected in the plankton of Gran Canaria Island, NE Atlantic, during the years 2005 and 2006, could only be identified as Chaceon spp. The temporal distribution of larval abundance suggested that main hatching periods of Chaceon spp. occur in spring and summer. These results are useful to better understand the reproductive strategies of these deep-water crabs, which in turn will be useful for future fishery management of this resource of increasing interest in the Canary Islands.